Application of ZnO nanoparticles in a self-cleaning coating on a metal panel: an assessment of environmental benefits - Stieberova, Barbora; Zilka, Miroslav; Ticha, Marie; Freiberg, Frantisek; Caramazana-Gonzalez, Pablo; McKechnie, Jon; Lester, Edward (American Chemical Society, 2017)
This article is focused on assessing environmental benefits of a self-cleaning coating (SCCs) containing nanoparticles (NPs) applied on metal panels. ZnO NPs are incorporated in the coating to enhance the level of hydrophobicity, which enables a dramatic reduction in the need for surface maintenance. The key question evaluated in this paper is whether the overall environmental performance of a nanobased SCC is better than the environmental performance of a coating without NPs. Much of the paper is dedicated to a comparison of advanced polyvinylidene fluoride (PVDF) protective coating with an alternative coating in which part of the PVDF is replaced by ZnO NPs. An integral part of the paper represents a detailed environmental assessment of the key ingredient of the nanoenhanced coating, ZnO NPs produced by large-scale supercritical hydrothermal synthesis developed within the Sustainable Hydrothermal Manufacturing of Nanomaterials (SHYMAN) project. LCA results show that the coating with NPs performs better than the coating without NPs in all assessed impact categories. This is due to the elimination of environmental impacts during the use stage where no maintenance is needed in the case of the coating with NPs. This reduction clearly outweighs the small additional environmental impacts of the production stage associated with the ZnO NPs.